2018
DOI: 10.21873/anticanres.12196
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Lidocaine on Human Breast Cancer Cells: An In Vitro and In Vivo Experimental Trial

Abstract: In agreement with the notion that local anesthesia may be beneficial for cancer therapy, lidocaine has a protective effect against breast cancer cells in experimental studies. However, the beneficial impact of local anesthetics on breast cancer needs to be strengthened by additional preclinical and clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 43 publications
(68 reference statements)
2
42
0
Order By: Relevance
“…Currently, growing researches have confirmed that lidocaine may perform anticancer effects on the therapy of diverse cancers through affecting tumor cell malignant behaviors, such as cell viability, apoptosis, migration and drug resistance. 4,8,21,22 In fact, sustaining proliferation and resisting apoptosis are two significant hallmarks of cancer cells that contribute to cancer cell malignant enlargement and progression, and proliferation inhibition and apoptosis promotion of cancer cells are promising methods to hinder the development of human cancers. 23 In this study, lidocaine up-regulated the proproliferative protein Cyclin D1 and pro-apoptotic proteins cleaved-Caspase-3 and cleaved-Caspase-9, which Figure 7 Lidocaine mediates CRC cell viability loss, apoptosis induction and aerobic glycolysis suppression by regulating miR-138-5p/HEY1 axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, growing researches have confirmed that lidocaine may perform anticancer effects on the therapy of diverse cancers through affecting tumor cell malignant behaviors, such as cell viability, apoptosis, migration and drug resistance. 4,8,21,22 In fact, sustaining proliferation and resisting apoptosis are two significant hallmarks of cancer cells that contribute to cancer cell malignant enlargement and progression, and proliferation inhibition and apoptosis promotion of cancer cells are promising methods to hinder the development of human cancers. 23 In this study, lidocaine up-regulated the proproliferative protein Cyclin D1 and pro-apoptotic proteins cleaved-Caspase-3 and cleaved-Caspase-9, which Figure 7 Lidocaine mediates CRC cell viability loss, apoptosis induction and aerobic glycolysis suppression by regulating miR-138-5p/HEY1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, in addition to multiple anesthetic effects, emerging evidence has identified the antitumor effects of lidocaine in many cancers. 8 For example, lidocaine suppressed lung cancer cell proliferation by modulating the inhibition of GOLT1A. 4 Lidocaine performed anti-proliferative and apoptotic effects by regulating p53 expression in hepatocarcinoma cells to suppress tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as per the safety profile, lidocaine not only shows well-tolerant toxicity ( Yang X. et al, 2018 ), selectivity in killing cancer cells over normal cells ( Chamaraux-Tran et al, 2018 ), but also may alleviate cisplatin-induced body loss in the animal studies ( Gao et al, 2018 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Given lidocaine’s effect in suppressing metastasis, its further application in various breast cancer cell lines, including normal breast epithelial cells MCF-10A, luminal breast cancer cell MCF-7, TNBC MDA-MB-231, and SKBr3 human epidermal growth factor receptor 2 (HER2) positive cells and in MDA-MB-231 cells xenograft model at clinically relevant concentrations were studied ( Chamaraux-Tran et al, 2018 ). Lidocaine (0.1–10 mM determined by MTT assay) showed selectivity in suppressing the viability and migration of cancer cells over normal cells.…”
Section: Lidocaine In Cancer Treatmentmentioning
confidence: 99%
“…In addition, lidocaine produces DNA demethylation in breast cancer cells in vitro [ 68 ]. Moreover, lidocaine, ropivacaine and bupivacaine reduce cell proliferation at concentrations of 100 μM, leading to cell cycle delay or arrest at G0/S-1 phases [ 69 ].…”
Section: Effects Of Anaesthetic Agents On Immune Function and Tumour mentioning
confidence: 99%